2017
DOI: 10.4236/ojpsych.2017.74032
|View full text |Cite
|
Sign up to set email alerts
|

Management of Post-Traumatic Stress (PTSD) Dementia and Other Neuro-Degenerative Disease with Photo-Medicine: Clinical Experience and Case Studies

Abstract: Objective: Photobiomodulation (also known as Low Level Laser. LLLT or Cold Laser; Photo Medicine (PM)) has been a vital adjunct therapy in our clinical practice over 5 years, observations of improvement in cognition and personality were noted in several patients. As a result, selected patients with Alzheimer's Disease, vascular dementia, post-traumatic brain injury and other neuro-degenerative diseases were treated at clinical practices in Buffalo, New York; Sarasota, Florida; Lafayette, Indiana; Phoenix, Az.,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…The authors note a decrease in the severity of headache, sleep disorders, accelerated normalization of cognitive functions, elimination of symptoms of depression, anxiety and irritability. Similar data were obtained by W. Stephan et al (2017) for patients with posttraumatic stress disorder [42], which was confirmed by later experimental studies by H. Zhao et al (2023) [47]. An unusual clinical effect, considered by A.…”
Section: Possibilities Of Photobiomodulation In Neurological and Psyc...supporting
confidence: 82%
See 1 more Smart Citation
“…The authors note a decrease in the severity of headache, sleep disorders, accelerated normalization of cognitive functions, elimination of symptoms of depression, anxiety and irritability. Similar data were obtained by W. Stephan et al (2017) for patients with posttraumatic stress disorder [42], which was confirmed by later experimental studies by H. Zhao et al (2023) [47]. An unusual clinical effect, considered by A.…”
Section: Possibilities Of Photobiomodulation In Neurological and Psyc...supporting
confidence: 82%
“…It is known that the nature of the biological effects of light radiation is determined by its parameters, primarily wavelength, power and energy, and monochromaticity, coherence and collimation are also important for laser radiation [5,42]. Most ranges of visible light (in particular, those recognized by human vision as blue and green) realize their effect through modification of the state of ion channels.…”
Section: Molecular and Cellular Mechanisms Of Action Of Red And Infra...mentioning
confidence: 99%
“…Our most recent papers described the clinical improvement in patients treated with our laser system for Post-traumatic Stress Disorder (PTSD) as well as for mild dementia [15] [16]. We have also recently obtained positive results in a case study of children and adults with attention deficit hyperactivity disorder (ADHD) [17].…”
Section: Introductionmentioning
confidence: 99%
“…However, for the last few years they have started to treat brain disorders, and so far have published three sets of case studies describing the benefits of transcranial LLLT. These comprise a serious case of traumatic brain injury [13], and two sets of cases in patients suffering from dementia and post-traumatic stress disorder [14] [15].…”
Section: Introductionmentioning
confidence: 99%